Hubungan Ekosistem Marin Pinggir Pantai dan Muara Sungai Dengan Sosio-Ekonomi Komuniti Nelayan di Teluk Brunei dan Teluk Padas, Sabah: Satu Tinjauan - Ismail Ali; Mohammad Raduan Mohd. Ariff (2007)
Brunei Bay, with an area of about 3,000 square kilometres and billowed by the SouthChina Sea, is rich in various flora and fauna and important to the fishing communityliving in the coastal area and river estuary of Brunei Bay and Padas Bay. This paperaims to study the status of the coastal marine and river estuary ecosystems and to whatextent the action of the fishing and private communities has given impact to the coastalmarine and river estuary ecosystems in Brunei Bay. To accomplish this study, severalobjectives were outlined such as to study the physical characteristics of the coast andthe sea in Brunei Bay, background, number, and income of the fishermen; fishing activities,ownership of boat and engine, fishing methods used, types of fish caught and oil andice facilities; landing and marketing including number of arrests, role of middlemen, jetty landing facilities, fish marketing activities, market price; role of the Department of Fisheries and Lembaga Kemajuan Ikan Malaysia (LKIM) in overseeing the fishing industryand improving the living standards of fishermen in Brunei Bay; current problems faced by the fishing industry and finally the status of the marine ecosystem of Brunei Bay.Studies regarding the relationship between the marine ecosystem and the existence of the fishing community include coastal areas and estuaries and involved 73 respondentsfrom 14 fishing villages in Brunei Bay and Padas Bay.